A coloured Petri net analysis of the Transaction Internet Protocol. (28th January 2011) - Georgiadis, Christos K.; Pimenidis, Elias; Kokkinidis, Ioannis
The Transaction Internet Protocol (TIP) aims at facilitating e-commerce by enforcing atomicity guarantees in transactions distributed between several autonomous transaction processing systems. In this work, the authors explore a holiday booking scenario in which a customer is protected by the TIP such as to prevent ending up with a hotel reservation without the requested flight reservation i.e. enclosed in the same holiday package. In fact, TIP defines an approach that makes the commit processing independent of the communication protocol used, but there are a number of potential pitfalls that make it useful to provide a formal approach to reason about the behavioural properties of TIP. The authors propose a coloured Petri net model that allows interactive simulation and verification of correctness properties within the CPN-tools modelling environment. Representative results for the generated reachability graph, providing an insight into the model's structural properties are shown at the end of this paper. The model can be used in the CPN-tools environment for model checking tasks, where the properties of interest can be expressed in graph exploration or temporal logic-based state space queries.